Budgeting as a Controlling Instrument in Company Management - Nita , Bartłomiej (Studia Oeconomica Posnaniensia, 2014)
This paper discusses the control function of budgeting. The first section explains the cybernetic approach to control in the area of management accounting according to R.N. Anthony, as well as the approaches of other accounting researchers. The author highlights the multi-faceted nature of control and elaborates a broad understanding of its functions that goes beyond a narrow interpretation of the term "control" as meaning a simple comparison of the actual situation with planned outcomes. In the second part, the author argues that budgeting is an important instrument of control aimed at achieving the objectives of a company. The mechanism for the identification and analysis of variance is also explained in relation to the concept of flexible budgeting based on the example of operating income.